PECULIARITIES OF CORN YIELD MANAGEMENT UNDER UNSTABLE MOISTENING - Marenych, M.M.; Kaplenko, V.O.; Koba, K.V.; Holub, O. R. (Scientific Progress & Innovations, 2019)
The following peculiarities of corn yield formation were studied in three-year experiment: yield analysis in crop rotation; the effect of pre-sowing seed treatment; the impact of fertilization system; sowing density and speed of sowing implement movement on the yield. It was established that using cattle manure as organ-ic fertilizers in the amount of 50 t/ha compensated the negative effect of undesirable proceeding crop, for example sunflower, under which this rate was applied. Corn yield in such case was the highest and made 9.7... 11.1 t/ha, the yield after corn was 9.4 … 10.5 t/ha. In case of applying considerable amount of fertiliz-ers, especially cattle manure, proceeding crops insufficiently influenced grain yield formation. For example, TM Pioneer corn hybrid yield after winter wheat made 9.83 t/ha on the average, and after sunflower – 10.2 t/ha, the difference was only 3.7 %. The lowest yield was obtained in case of sowing corn after the same crop on grain and silage – 9.3 and 9.57 t/ha, respectively. The lowest yield was observed at corn repeated sowing, which confirmed generalized previous experiments. It was established that under intensive applying organic-mineral fertilizers corn hybrids realized their genetic potential irrespective of cultivation year. Ap-plying nitrogen fertilizers’ rate in the amount of 150 kg/ha turned out to be the most effective not depending on the conditions of cultivation year. Pre-sowing seed treatment with a mixture of treaters and humic stimu-lating substances is the effective method of corn yield management. It enables considerably to form better root and above-ground parts and control plantlets’ affection by diseases. Under unstable moistening, the highest yield was achieved at sowing rate of 80 …85 thousand seeds per hectare. However it is expedient to substantiate sowing rates economically. 10 km/h is the optimal speed of implement movement for corn sow-ing. Decreasing or increasing this parameter led to yield decrease, which is explained by irregular seed dis-tribution in the soil. It is necessary to determine the speed depending on the implement technical characteris-tics and soil condition at the moment of sowing.